Inhaltliche Elemente und Anforderungsniveau des Unterrichtsgesprächs beim geometrischen Beweisen: Eine Analyse videografierter Unterrichtsstunden (mathematica didactica, 2004)
In this paper we present results of a descriptive video-based study on proof inthe mathematics classroom. The results indicate that so-called content elements of proof development focussing on the metacognitive understanding are hardly integrated in the processof developing proofs in class. Moreover, the discourse in the classrooms is often characterized by questions of the teacher on a low level of complexity.